Comparative heel stick study showed that newborn infants who had undergone repeated painful procedures showed increased short-term pain responses - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA (Blackwell Publishing Ltd, 2016)
Aim: We evaluated the short-term effect of repeated pain exposure on the pain responses of newborn infants using different pain assessment methods, as this area had been under-researched. Methods: We compared 20 term, large for gestational age infants and 40 term, appropriate for gestational age controls. All had undergone a heel stick for a newborn screening test just before discharge, but the larger babies had also undergone at least other five painful stimuli prior to that. A pulse oximeter and a skin conductance algesimeter (SCA) were connected to the babies during the heel prick, and video recordings were made. Crying time, the Neonatal Infant Pain Scale (NIPS), heart rate, peripheral oxygen saturation (SpO2) and SCA measurements were compared within and between the groups. Results: After the heel prick, the crying time (p = 0.021) and NIPS (p = 0.013) scores were significantly higher in the study group and the SpO2 levels were significantly lower (p = 0.009), but the heart rate (p = 0.981) was not significantly different between the groups. SCA measurements did not differ significantly between the groups. Conclusion: Babies who received more painful stimuli during the first few days of life showed greater pain responses during a subsequent heel prick. ©2016 Foundation Acta Pædiatrica. Published by John Wiley & Sons Ltd
Keywords: Neonatal Infant Pain Scale; Newborn; Pain; Recurrent pain; Skin conductance algesimeter